Nursing care in the patient with epilepsy/seizures - Liuba Hernandez Toledo; Maria de los Angeles Peña Figueredo; Lisette Miranda Lara; Juan E Bender del Busto (Archives of Nursing Practice and Care - Peertechz Publications, 2020)
Epilepsy is considered to be as old as humanity itself and one of the most common Central Nervous System disorders. It has been known since ancient times and is considered a modern disease. It is a global health problem and is affected by more than 50 million people, most of them from developing countries and with psychobiological consequences and even the risk of death, as part of its complications. Comprehensive management is necessary, which includes preventive / prophylactic, pharmacological and non-pharmacological treatment and, therefore, the training of nursing staff in specialized protocols is essential, to ensure adequate patient management, adequate quality of care and avoid complications preventable, which is set out in the document.